Promoting Community Based Waqf - Nor Asiah Mohamad (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2017)
Waqf represents religious commitment, economic stimulus, philanthropist mechanism, and also social unity thrust or force in any Muslim society in a Muslim or non Muslim country. This paper evaluates a special co-operative social philanthropist scheme known as infaq lil-waqf which provides opportunities for co-operative society to contribute employing the concept of waqf or Islamic endowment. The most important goal of the waqf product is to raise fund for projects that will enhance socio-economic status of cooperative as well as the general members of society. To achieve this goal, a special unit known as infaq lil waqf was established under National Co-Operative Movement of Malaysia (Angkasa). The participation from the co-operative society in Malaysia is very impressive. It has ventured into widen horizon of co-operative activities including business, education, welfare, health, real estate and Rest and Recreation Area. The benefit reaches beyond the members of the cooperative but the general public, Muslim and non Muslim alike. The Annual Report for Angkasa records a very promising and encouraging result of the scheme. As it is successful at national level, the scheme is also potential to be expanded at international level.